Assessment of Heavy Metal (As, Pb, Cd, Zn) Concentrations in the Hard Clam (Meretrix lyrata) from Selected Coastal Areas of Quang Ninh and Hai Phong, Vietnam - Van Nam, Le; Thanh Nghi, Duong; Van Quy, Tran; Huu Tuyen, Le; Thi Minh Trang, Pham; Thi Tuyet Anh, Pham; Thi Bich Linh, Tran; Thi Mai Ninh, Truong; Thi Mai Luu, Nguyen; Thi Thu Ha, Nguyen; Manh Hao, Do; Van Bach, Nguyen; et al. (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2SDO - 10.25073/2588-1094/vnuees.5421, 2025)
The study focuses on assessing the concentrations of heavy metals (As, Pb, Cd, Zn) in hard clam (Meretrix lyrata) collected from five coastal areas of Quang Ninh (Mong Cai, Ha Long) and Hai Phong (Do Son, Kien Hai, Hung Thang). The results showed that concentrations of As (2.6 - 3.31 µg/L), Pb (2.3 - 5.4 µg/L), and Cd (0.59 - 1.07 µg/L) in water samples were below the limits set by QCVN 10:2023/BTNMT, whereas Zn (216.15 - 878.7 µg/L) exceeded the threshold value of 100 µg/L. In clam tissues, As (0.19 - 0.25 mg/kg wet weight), Pb (0.114 - 0.178 mg/kg wet weight), Cd (0.98 - 1.34 mg/kg wet weight), and Zn (17.37 -21.75 mg/kg wet weight) were within the safety limits regulated by Decision No. 46/2007/QD-BYT, QCVN 8-2:2011/BYT, and WHO guidelines. The bioaccumulation factor (BAF) indicated that Cd had a bioaccumulation potential ranging from 915.89 to 1819.67 L/kg wet weight, whereas As, Pb, and Zn were below the threshold of 1,000 L/kg wet weight, showing no bioaccumulation. These findings suggest that hard clam (Meretrix lyrata) from the studied areas are safe for consumption; however, continuous monitoring of Cd levels in clam tissues and Zn pollution in water is recommended.